The plasma-chemical mechanism of surface destruction of the diagnostic system components inside EAST vacuum vessel - L.G. Lobanova; S. Wang; H. Lian; X. Cui; J. Chen; R. Yan; L. Zhang; V.P. Afanas’ev; H. Liu (Nuclear Materials and Energy)
The study investigates the causes of surface degradation of the retro reflectors, made of polycrystalline molybdenum, used in the optical diagnostic polarimeter/interferometer (POINT) system on the EAST tokamak. The component and depths profiling analysis of the retro reflectors surface was conducted based on the interpretation of X-ray photoelectron spectroscopy (XPS) energy spectra. The depths profiling analysis was performed using argon ion sputtering with an energy of 2 keV to a depth of 60 nm. On the uncleaned retro reflectors surface, the following was observed: the predominant presence of molybdenum trioxide (MoO3), no presence of unoxidized molybdenum, and the presence of elements from constructional details, including C and B, Zn, Fe, Cu, Ca, Na with quantities not exceeding 1 %. It was established that the main cause of surface degradation of the retro reflectors and, consequently, the degradation of their reflective properties, is the active chemical oxidation of molybdenum during technical breaks and in the absence of plasma discharges, followed by the plasma-chemical removing of molybdenum oxides under plasma discharge conditions. The cyclic process of surface oxidation by water vapor and oxygen and subsequent removing of molybdenum oxides due to the heating and the interaction of the retro reflectors surface with plasma, leads to the formation of a well-developed morphology on the retro reflectors surface and, thus, to the reflectivity degradation. It is noted that similar processes occur with inner vacuum vessel materials, which consist of transition metals, such as W and Mo.